2020
DOI: 10.20473/vol6iss20196pp1242-1258
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekspor Produk Halal terhadap Current Account Balance di Indonesia

Abstract: This research aims to measuring the effects of halalproduct export on current account balance (CAB) with some of control variables such as GDP growth, national currency to US dollar exchange rate, government expenditure, real interest rate and inflation. This research is quantitative approach using ARDL model. Based on time series data in quarterly, The results of the t and F tests in this study indicate that in the long run the export of halal industrial products and government expenditures partially has a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…The same results were also expressed by research conducted by Mayong and M Handry [22]. And for the halal product category, there is research conducted by Wina and Scientists which revealed that exports of halal industrial products and government spending had a positive and significant effect on the current account balance in Indonesia 2008-2017 [23], and Syamsuri et al who revealed that exports of halal products had a positive effect and halal imports had a negative and significant effect on the current account in OIC countries 2015-2019 [ 24]. This shows that the value of a country's current account is very important because it shows the country's export and import conditions which will inform that the country is experiencing a current account surplus or deficit which will affect the state of the country's economy.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The same results were also expressed by research conducted by Mayong and M Handry [22]. And for the halal product category, there is research conducted by Wina and Scientists which revealed that exports of halal industrial products and government spending had a positive and significant effect on the current account balance in Indonesia 2008-2017 [23], and Syamsuri et al who revealed that exports of halal products had a positive effect and halal imports had a negative and significant effect on the current account in OIC countries 2015-2019 [ 24]. This shows that the value of a country's current account is very important because it shows the country's export and import conditions which will inform that the country is experiencing a current account surplus or deficit which will affect the state of the country's economy.…”
Section: Introductionsupporting
confidence: 62%
“…Similar results were also expressed by Wina and Scientists who conducted research in Indonesia, where the export value of halal products had a positive and significant effect on the current account value in Indonesia. [23].…”
Section: Best Model Selection Resultsmentioning
confidence: 99%
“…Halal Industry is a new potential growth sector in the global economy. (Purnama & Auwalin, 2020) The Industry is growing at 20 percent per year estimating a value of US $560 billion and the total estimated value is US$2.3 trillion excluding Islamic Finance. The Industry is spreading like wings in the global economy rapidly, it is not limited to 1.8 billion Muslims only but also to the non-Muslim market.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide demand against halal food not only from Muslims but also because of rising consumer preference of Non-Muslims to consume halal products (Badi, 2019) The Halal industry is growing rapidly based on the increasing demand for halal products in line with the growth of Muslims in the world. (Purnama & Auwalin, 2020). The current Muslim population is 2.18 billionn which is 28.26% of the total population is increasing at 1.84% a year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation